Teacher’s stories about teaching newly arrived refugee youths at a vocational upper secondary school in Sweden - Hamid Asghari (Educare)
This article presents the stories of four teachers teaching newly arrived refugee youths at a vocational upper secondary school. The youths came to Sweden in 2015 and later, and they live in a so-called vulnerable area. This is a period when many unaccompanied children and adolescent refugees arrived in Sweden. The study aims to contribute to knowledge about teaching newly arrived refugee youths and the way these youths can influence teaching in a vocational school. The methodological and theoretical starting point for the study is based on a narrative perspective. The stories are analysed thematically and show that these students have great solidarity with each other, are ambitious, and create a good mood in the classroom. In addition, there is always “someone” who does not believe in democratic values, although most of the students value the Swedish democracy and equality between men and women. The expulsion decision that some students receive affects the teachers’ teaching as well, since it means that they also have to deal with teaching situations where their students’ lives and deaths are involved in the sense that they are refugees threatened by expulsion.